CHANGES IN THE FIELD OF TERMINOLOGY AND METHODS OF TRANSLATION OF TERMS IN ENGLISH - Ne'matova Manzura Nurxonovna (TADQIQOTLAR.UZ, 2024)
Abstract: Different topics are currently in the focus of world linguistics together with the terminology. It is in this period that modern linguistics to find "terminology" that has acquired a wider meaning and is studied more deeply is one of the most difficult tasks.